The role of residual char on ash flow behavior, Part 1: The effect of graphitization degree of residual char on ash fusibility. (15th December 2018) - Wang, Ji; Kong, Lingxue; Bai, Jin; Li, Huaizhu; Bai, Zongqing; Li, Xian; Li, Wen
Highlights: The residual char graphization degree influences ash fusion behavior. The high graphization degree of char hinders the carbothermal reaction. The peak temperatures of carbothermal reaction increase with graphitization. The residual char benefits the formation of FeSi, also increases AFTs. Abstract: Residual char is widely found in the slag from gasifier, which significantly influences the ash fusibility due to carbothermal reaction. Residual char has different graphitization degree owing to the residence time and operating temperature of the gasifier, while the effect of graphitization degree of residual char on ash fusibility and carbothermal reaction is still unknown. In this work, graphite, activated carbon and high temperature demineralized coal char were selected to investigate the effect of graphitization degree of residual char on ash fusibility under an Ar atmosphere. X-ray diffraction (XRD) and Siroquant software were used to investigate the mineral transformation of the ashes with residual char at high temperatures. Thermogravimetric combined with mass spectrum and differential thermal analysis (TG-MS-DSC) were used to study the effect of graphitization degree of residual char on mineral and carbothermal reaction during heating. When the ash contains same content of residual char, the ash fusion temperatures (AFTs) increase as the graphitization degree of residual char increases. The influence by residual char is more obvious when the mass fraction exceeds 5%. The increase of graphitization degree of residual char impedes the mineral reaction and the carbothermal reaction. The initial temperature of the mineral reaction increases from 1229.3 °C to 1247.2 °C and 1260.4 °C for the ashes with activated carbon, coal char, and graphite, respectively. The peak temperatures of the carbothermal reaction are 1306, 1319 and 1339 °C. At the temperature below 1300 °C, the increase of AFTs is attributed to the increase in the content of cristobalite, and the decrease in the content of anorthite. Above 1300 °C, the increase of AFTs is caused by the increase of the amount of unreacted residual char. Besides, the residual char benefits the formation of FeSi, which also leads to increases of the AFTs.